# Solve the initial value problem below using the method of Laplace transforms. y'' - 12y' +45y...

Solve the initial value problem below using the method of Laplace transforms. y'' - 12y' +45y = 39 e 4t, y(0) = 3, y'(0) = 15 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. y(t) = (Type an exact answer in terms of e.)

If you have any questions please let me know

Thank you

##### Add Answer of: Solve the initial value problem below using the method of Laplace transforms. y'' - 12y' +45y...
Similar Homework Help Questions
• ### Solve the initial value problem below using the method of Laplace transforms. y"' + y' -...

Solve the initial value problem below using the method of Laplace transforms. y"' + y' - 20y = 0, y(0) = -1, y'(0) = 32 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. y(t) = (Type an exact answer in terms of e.)

• ### Solve the initial value problem below using the method of Laplace transforms. y" - 2y' -...

Solve the initial value problem below using the method of Laplace transforms. y" - 2y' - 3y = 0, y(0) = -1, y' (O) = 17 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms y(t) = 1 (Type an exact answer in terms of e.)

please please please answer all! its very appreciated! Solve the initial value problem below using the method of Laplace transforms. y'' + 4y' - 12y = 0, y(0) = 2, y' (O) = 36 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. y(t) = 0 (Type an exact answer in terms of e.) Solve the initial value problem below using the method of Laplace transforms. y'' - 8y'...

• ### Solve the initial value problem below using the method of Laplace transforms. 4ty'' - 6ty' +...

Solve the initial value problem below using the method of Laplace transforms. 4ty'' - 6ty' + 6y = 36, y(0) = 6, y'(0) = -1 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. y(t) =

• ### Solve the initial value problem below using the method of Laplace transforms. 2ty" - 5ty' +...

Solve the initial value problem below using the method of Laplace transforms. 2ty" - 5ty' + 5y = 20, y(0) = 4, y'0) = -3 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. y(t) =

• ### 7.6.27 Solve the given initial value problem using the method of Laplace transforms. z"' + 6z'...

7.6.27 Solve the given initial value problem using the method of Laplace transforms. z"' + 6z' + 8z = e-bu(t-1); Z(0) = 2, z'(0) = -6 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms Solve the given initial value problem. z(t)=

• ### Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below...

Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below y+2yt22, y(0) = 0, y'(0) = - 2 Click here to view the table of Laplace transforms Click here to view the table of properties of Laplace transforms Y(s)= Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below y+2yt22, y(0) = 0, y'(0) = - 2 Click here to view the table of Laplace transforms Click here...

• ### Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below....

Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below. y" + 4y = 512 - 2. y(0)=0, 7(0) = -8 Click here to view the table of Laplace transforms Click here to view the table of properties of Laplace transforms. Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below. y" + 4y = 5t2 - 2. y(0) = 0, y'(O) = - 8 Click here to...

• ### Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below....

Solve for Y(s), the Laplace transform of the solution y(t) to the initial value problem below. y'' +6y=t? - 2, y(0) = 0, y'(0) = -5 Click here to view the table of Laplace transforms. Click here to view the table of properties of Laplace transforms. Y(s)=

• ### Solve the initial value problem below using the method of Laplace transforms. ka Type an exact an...

Solve the initial value problem below using the method of Laplace transforms. ka Type an exact answer in terms ofe) Solve the initial value problem below using the method of Laplace transforms. ka Type an exact answer in terms ofe)

Free Homework App